Angelika Neuwirth's Feminist Hermeneutics of Q.S. Āli 'Imrān (3): 7: The Interpretation of Mutasyābihāt Verses and Muḥkamāt Verses - Wildan Fahdika Ahmad (Universitas Islam Negeri Sunan Kalijaga, 2025)
The reading of Q.S. Āli 'Imrān (3): 7, especially in relation to mutasyābihāt verses (similar, vague, similar to one another, cannot stand alone) and muḥkamāt verses (definite, firm, clear), generally have nothing to do with gender issues. With a critical approach, especially literary and historical approaches, Angelika Neuwirth presents a different interpretation, which implicitly displays the Hermeneutics of Feminism, where muḥkamāt verses and mutasyābihāt verses can be positioned as a discourse of gender equality. This research aims to develop the muḥkamāt-mutasyābihāt theory from Angelika Neuwirth's perspective. The method used is the “qualitative grounded theory” method. The research data is obtained through library research, which is taken from data sources in the form of writings or statements of Angelika Neuwirth regarding Q.S. Āli 'Imrān (3): 7, as well as data from other sources related to muḥkamāt-mutasyābihāt verses. The data collected were then analyzed and interpreted in such a way. The results show that the reading of Q.S. Āli 'Imrān (3): 7 is closely related to feminist hermeneutics, and therefore has evolved.